2022
DOI: 10.3389/fsoc.2022.841847
|View full text |Cite
|
Sign up to set email alerts
|

Language Choices at Home and Their Relationship With Educational Outcomes, With a Special Focus on Children With Origins in Former Yugoslavia and Turkey in Six European Countries

Abstract: Language has been conceptualized as both a measure as well as a predictor of integration among immigrants and their children. However, the relationship between language spoken at home and different educational outcomes remains poorly understood. Many studies indicate that nurturing students' first languages is positively associated with their learning at school. Other research suggests that one of the reasons why children of immigrants tend to perform worse at school is due to speaking a language other than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
0
1
0
Order By: Relevance
“…However, in the present study, we did not collect data to distinguish whether respondents were newcomers because we only asked children about the languages used at home, and it is not clear whether the immigrant paradox can explain our results. Furthermore, we did not collect data on factors that may influence the use of multiple languages at home, such as length of stay in Japan, the nationality of their parents, their parents and siblings speaking Japanese in the home, the socioeconomic status of the family, and the school environment, 28 , 29 , 30 , 31 , 32 therefore we cannot estimate the actual level of enculturation to Japan of children who use foreign languages at home. Nevertheless, we demonstrated the poorer mental health status of children who used both languages at home.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, we did not collect data to distinguish whether respondents were newcomers because we only asked children about the languages used at home, and it is not clear whether the immigrant paradox can explain our results. Furthermore, we did not collect data on factors that may influence the use of multiple languages at home, such as length of stay in Japan, the nationality of their parents, their parents and siblings speaking Japanese in the home, the socioeconomic status of the family, and the school environment, 28 , 29 , 30 , 31 , 32 therefore we cannot estimate the actual level of enculturation to Japan of children who use foreign languages at home. Nevertheless, we demonstrated the poorer mental health status of children who used both languages at home.…”
Section: Discussionmentioning
confidence: 99%
“…That study also pointed out that parents should be encouraged to study Japanese to help to communicate with supporters and teachers of their children (Nguyen, 2017). Similarly, study from Europe indicated that, though language shift at home and school are common for immigrants, linguistically responsive pedagogies and positive school climate, that is, more diverse school environment can contribute on education of newly-arrived immigrants the most (Kilpi-Jakonen & Alisaari‌, 2022). Another study also revealed the beneficial effect of bilingual instruction at school (English + Spanish) on academics of Latino immigrant children (Collins, 2014).…”
Section: Discussionmentioning
confidence: 99%